THE ANXIETY LEVELS WOMEN ELDERLY IN CLIMAXTERIUM PERIOD AT PUBLIC HEALTH CENTER SOUTH ALALAK BANJARMASIN - Margareta Martini; Margareta Rosa Peni; Icha Inara (Universitas Sari Mulia, 2015)
Background: Climaxterium period is signed with the decrease of estrogen level and the increase of gonadotropin excess. This lack of estrogen hormone causes the decline of the variety of either degenerative function or endocrinology from ovarium. Disturbances can be either physical or psychological cause of anxiety to most women. Such complaint in this period is a result ofclimacteric syndrome.Objective: To know about how the description of anxiety levels elderly women in climaxterium period at Public Health Center South Alalak Banjarmasin.Methodology: Type of quantitative research to take data sampling in using proportionate stratified random sampling technique with the descriptive research design of a number of samples as many as 198 respondents. The instrument to take data use questioner and the data analysis use frequency distribution and proportion.Result: The result showed that was anxiety level of elderly women premenopause are moderate anxiety (48,9%), the anxiety level of elderly women menopause are mild anxiety (66,7%), the anxiety level of elderly women, postmenopause are mild anxiety (84,4%).Conclusion: Based on our research the majority of elderly women in climaxterium period are mild anxiety and moderate anxiety.Keywords: Anxiety levels, elderly women in climaxterium period.